The Palgrave Handbook of Global Political Psychology - Dekker, H. author. aut Link
XIX, 475 p.
Keywords: This collection recalibrates the study of political psychology through detailed and much needed analysis of the discipline's most important and hotly contested issues. It advances our understanding of the psychological mechanisms that drive political phenomena while showcasing a range of approaches in the study of these phenomena.